Precedentes judiciais : aspectos controvertidos de sua aplicação no ordenamento jurídico brasileiro e o risco do discurso de fundamentação descontextualizado - Rosa, Fernanda Néri (2016)
This work aims to verify the controversial use of judicial precedent in Brazil and the risk of decisions on the ground out of context. The search begins with the origins of the legal traditions common law and civil law. Then points out some positive aspects of the institute\'s application in Brazil, especially its legal effects. After exposes points that deserve criticism, especially in its application, riddled with generic and decontextualized content, with the intention to solve the slow pace of justice. The issue presented is: judicial precedents are used appropriately? It has as main objective to analyze the judicial precedents and their application in the Brazilian legal system and specific, positive and negative aspects in the procedural practice. Delimits to the area of concentration Fundamental Rights and Guarantees, in that it addresses the risk of violation of the constitutional principles of equality, when you have separate trials for the same cases, access to justice, when it hinders the right of action of claimants , reasons for decisions when it goes to the foundation of several previous decisions of the case and legal certainty, when frustrated the applicant\'s expectations that trust certain jurisprudential understanding. The line of research is Ptotection Legal and Public Policy, since it deals with the current judicial function in the Brazilian legal system, their bases, their duties and their contradictions. The research is guided by the traditions of common law and civil law of the nineteenth until nowadays. The research technique is literature and documents through the study of the doctrine and judged. The theoretical framework is Lenio Luiz Streck, with the statement that the precedents are ready decisions. The results are: the influence of the common law tradition in the Brazilian legal system, the previous application of the advantages, and the presence of ruled in previous decisions, susceptible to decontextualized judgments.